UTILIZATION OF REGIONAL ASSETS: APPROACH IN DETERMINING ASSET UTILIZATION PATTERN - Benjamin Bukit, (International Journal of Innovations in Engineering Research and Technology, 2021)
Utilization of Regional Assets or Utilization of Regional Property is the utilization of BMD that is not used for carrying out the duties and functions of regional work units and/or optimizing Regional Property without changing its ownership status. Utilization of BMD provides opportunities for regions to increase local revenue and improve public facilities. The formulation of the problem in this study is the concept of asset utilization in increasing local revenue, methods of asset utilization, determination of contributions, and case studies of selecting asset utilization methods in the development of archipelagic tourism areas. This study uses a theoretical approach in explaining the concepts and methods of BMD utilization and uses research data in discussing case studies on the selection of BMD utilization methods. This paper aims to provide an overview of the use of regional property and its benefits in increasing PAD. The results of the discussion show that there are 5 methods of asset utilization, namely lease, borrow and use, utilization cooperation, build to handover, build handover, and infrastructure cooperation which each have their own goals, advantages and characteristics. In the context of increasing local revenue, each method of asset utilization (except borrowing and use) has its own form of contribution that is able to increase regional income and/or increase regional assets. The choice of asset utilization method should be based on the regional vision and mission as well as the most effective method has the greatest impact on regional economic growth.